2011
DOI: 10.1021/jo102361h
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective α-Amination of Branched Aldehydes Promoted by Simple Chiral Primary Amino Acids

Abstract: A series of simple chiral primary amino acids were first successfully applied to promote the enantioselective α-amination of branched aldehydes with azadicarboxylates and the desired adducts bearing quaternary stereogenic centers were obtained in excellent yields (up to 99%) and enantioselectivities (up to 97% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 73 publications
0
16
0
Order By: Relevance
“…On the other hand, our group is interested in developing new methods to construct substituted amino aldehydes and successfully applied chiral thioureas, amino acids in the amination of aldehydes with excellent results. 16, 18, 15j Based on these achievements and our continuing interests in asymmetric synthesis promoted by chiral amine catalysis, herein we report the asymmetric α‐amination of branched aldehydes with azodicarboxylates catalyzed by simple chiral imide monosubstituted 1,2‐diamine derivatives in excellent enantioselectivities.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, our group is interested in developing new methods to construct substituted amino aldehydes and successfully applied chiral thioureas, amino acids in the amination of aldehydes with excellent results. 16, 18, 15j Based on these achievements and our continuing interests in asymmetric synthesis promoted by chiral amine catalysis, herein we report the asymmetric α‐amination of branched aldehydes with azodicarboxylates catalyzed by simple chiral imide monosubstituted 1,2‐diamine derivatives in excellent enantioselectivities.…”
Section: Resultsmentioning
confidence: 99%
“…After that, an ion pair catalyst of 9‐amino(9‐deoxy)epi‐quinine and (‐)‐CSA was applied in this transformation . And in 2011, our group disclosed that the simple primary amino acid of 3‐(1‐naphthyl) alanine may catalyze the amination of branched aldehydes with high enantioselectivities . Even so the direct enantioselective preparations of unnatural chiral α‐amino acids, especially chiral quaternary amino acids, are still challenges.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Wang group later reported that a naphthyl-containing amino acid (C53) was a better catalyst for this amination reaction (Scheme 61). [76] Notably, C53 (20 mol %) promoted the reaction efficiently to provide the desired adducts 189 in high yields and stereoselectivities in most cases. In 2009, Maruoka and co-workers reported asymmetric a-amination of various b-ketoesters (190) with azodicarboxylate 188 in the presence of axially chiral phosphonium bromide C54 as a chiral catalyst and KH 2 PO 4 as a base (Scheme 62).…”
Section: à N Bond Formation By A-amination Of Tertiary A-carboxylatesmentioning
confidence: 99%
“…In 2010, Rawal et al developed the chiral squaramide organocatlyst derived from cyclohexane-1,2-diamine, which shown excellent catalytic performance in asymmetric a-hydrazination of 1,3-dicarbonyl compounds with azodicarboxylates [15]. More recently, Wang reported the amine-thiourea organocatalyst catalyzed the asymmetric amination of cyclic b-keto esters reaction [16]. Despite the progress has been made in recent years, the enantioselctive a-amination reaction catalyzed by BINOL-squaramides has been rarely described.…”
Section: Introductionmentioning
confidence: 99%